Bats, elephants, and their food: a conservation perspective on trophic interactions in the Namib Desert - Laverty, Theresa Marie, author; Berger, Joel, advisor; Crooks, Kevin, committee member; Wittemyer, George, committee member; Teel, Tara, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.